The relationships between lens diameter and ocular biometric parameters: an ultrasound biomicroscopy-based study - Huang, Zhiqian; Qi, Jiao; Cheng, Kaiwen; Liu, Shuyu; Zhang, Keke; Du, Yu; Lu, Yi; Zhu, Xiangjia (Frontiers in Medicine, 2024)
Purpose This study aims to explore the relationships between lens diameter (LD) measured with ultrasound biomicroscopy (UBM) and ocular biometric parameters. Methods Ocular biometric parameters including axial length (AL), white-to-white distance (WTW), anterior chamber depth (ACD), lens thickness (LT) and anterior segment length (ASL) were measured with IOL-Master 700, and the direct measurement of LD was conducted through UBM (ArcScan Insight 100). Relationships between LD and ocular biometric parameters were then investigated. Eyes with AL ≥ 28 mm were defined as eyes with extreme myopia, and eyes with AL < 28 mm were defined as eyes without extreme myopia. Results A total of 194 eyes from 194 subjects were included. The mean LD was 9.58 ± 0.49 mm, ranging from 8.60 to 10.96 mm. According to univariate analysis, larger LD was associated with elder age, male gender, larger WTW, ACD and ASL (all p < 0.05). Meanwhile, the LD was positively correlated with AL in eyes without extreme myopia (p < 0.05), but not in eyes with extreme myopia (p > 0.05). Backward stepwise regressions revealed that a larger LD was associated with larger WTW, ASL and AL in eyes without extreme myopia (all p < 0.05), while ASL was the only significant variable in eyes with extreme myopia (p < 0.05). Conclusion Larger WTW, ASL and AL in eyes without extreme myopia, as well as longer ASL in eyes with extreme myopia indicated a larger LD, which provides guidance in personalized surgical choice and promises ideal visual outcomes.